Studies on the Organocatalytic Enantioselective Michael Addition of Cyclic Ketones and α,α-Disubstituted Aldehydes to α-Nitrostyrenes - Annadate, Ritesh A.; N. V. G., Moorthy; Pansare, Sunil V. (Current Organocatalysis, 2018)
Background: The catalytic asymmetric Michael addition of carbonyl compounds to nitrostyrenes is of interest because the reaction establishes two adjacent stereocenters in one step and the product γ-nitrocarbonyl compounds are synthetically useful intermediates. This reaction has been exhaustively investigated with β-nitrostyrenes as the Michael acceptors but the use of α-nitrostyrenes, for establishing nonadjacent stereocenters in the product, is not well studied. Objective: The aim of this study was to investigate the organocatalytic asymmetric, enamine mediated, Michael addition of cyclic ketones and α,α-disubstituted aldehydes to in situ generated α- nitrostyrenes and to optimize the diastereoselectivity and the enantioselectivity of the reaction. Method: The Michael addition reactions of a series of ketones and aldehydes with a variety of α- nitrostyrenes, that were generated in situ form nitroacetates, were conducted in a selection of solvents in the presence of chiral pyrrolidine catalysts and protic acid additives. Conditions that provided the highest asymmetric induction were identified. Results: Under optimized conditions, γ-nitroketones (up to 99% ee) and γ-nitroaldehydes (up to 79% ee) were obtained. The synthetic utility of the γ-nitroladehydes was demonstrated by converting a representative Michael adduct into a functionalized pyrrolidine. Conclusion: The enamine mediated Michael addition of cyclic ketones and α,α-disubstituted aldehydes to in situ generated α-nitrostyrenes proceeds with moderate to good levels of 1,3-asymmetric induction. The methodology complements the well-known Michael addition reactions of β- nitrostyrene, and provides access to enantiomerically enriched γ-aryl-γ-nitro ketones and γ-aryl-γ-nitro aldehydes.
Keywords: Michael addition